Glutaraldehyde Crosslinked Alginate-Chitosan Nanoparticles as Paracetamol Adsorbent - Nurmala Nurmala; Adhitasari Suratman; Suherman Suherman (Universitas Gadjah Mada, 2023)
Paracetamol contained in wastewater can cause adverse effects on animal ecosystems, such as fish living in waters and cause harmful effects on humans. Adsorption techniques are used to remove these pharmaceutical compounds. Alginate-chitosan nanoparticles are non-toxic and effectively used as adsorbents to remove pharmaceutical compounds in wastewater. Research on glutaraldehyde crosslinked alginate-chitosan nanoparticles as paracetamol adsorbent has been carried out. This research used the ionic gelation method. Nanoparticles were characterized using transmission electron microscopy (TEM), scanning electron microscope (SEM-EDX) and Fourier transform infra-red spectrophotometer (FTIR). Furthermore, the nanoparticles were used for paracetamol adsorption. The results showed that the form nanoparticles are coarse solid powder and brownish yellow. The TEM image shows an average nanoparticle size of 8.22 nm. Glutaraldehyde crosslinked alginate-chitosan nanoparticles adsorbed paracetamol with adsorption kinetics followed a pseudo-second-order or Ho-McKay model, the adsorption rate constant of 0.0324 g mg−1 min−1. The isotherm study of paracetamol adsorption by glutaraldehyde cross-linked alginate-chitosan nanoparticles followed the isotherm Dubinin-Radushkevich isotherm model with a free energy value of 707.1068 kJ mol−1, and this value indicates the adsorption process by chemically or chemisorption.